Study on Indonesia Consumer Trust on Online Transaction - Asto Sunu Subroto (Sekolah Tinggi Manajemen IPMI, 2018)
Indonesian consumer who connected to the internet in 2016 reach 90,5 million. The numbers of consumer who transact online reach 26.3 million or 29% of the internet users. Based on the research, the readiness of internet user for e-commerce transaction reaches more than 85%. However, there is still challenge in trust. In the same prices, consumers still prefer to shop ofline. Level of trust is divided into four categories, involve trust to the e-commerce industries in general, trust to the ordered and delivered the product, trust to the security of payment, and trust to the courier company. Due to trust becomes a most important factor in an online transaction, research about it have to be conducted periodically, so readiness ofIndonesian to the online transaction can be tracked. The result of the research is to not only for e-commerce industries but also for the traditional trade (ofline) industries and economy ofIndonesia.